Artemisitene activates the Nrf2‐dependent antioxidant response and protects against bleomycin‐induced lung injury. Issue 7 (22nd March 2016) - Chen, Weimin; Li, Shanshan; Li, Jinwei; Zhou, Wen; Wu, Shouhai; Xu, Shengmei; Cui, Ke; Zhang, Donna D.; Liu, Bo
ABSTRACT: The transcription factor nuclear factor erythroid 2‐related factor 2 (Nrf2) is a crucial regulator of the cellular antioxidant response and xenobiotic metabolism. Activation of the Nrf2 signaling pathway has been demonstrated to confer protection against environmental insults and prevent disease or inhibit the progression of diseases related to oxidative stress. In an attempt to identify novel improved Nrf2 inducers for systemic protection against tissue damage by environmental insults, we identified artemisitene as a novel Nrf2 activator using antioxidant responsive element luciferase assay in MDA‐MB‐231 cells. Further studies suggest that artemisitene activates Nrf2 by decreasing Nrf2 ubiquitination and increasing its stability. In Nrf2 wild‐type mice, systemic administration of artemisitene strongly inhibits bleomycin‐induced lung damage. Artemisitene represents a novel class of Nrf2 inducer, and artemisitene‐based therapeutic approach targeting Nrf2 may also provide antioxidant protection for humans against tissue damage by toxic chemicals.— Chen, W., Li, S., Li, J., Zhou, W., Wu, S., Xu, S., Cui, K., Zhang, D. D., Liu, B. Artemisitene activates the Nrf2‐dependent antioxidant response and protects against bleomycin‐induced lung injury. FASEB J. 30, 2500‐2510 (2016). www.fasebj.org